Determination of polybrominated diphenyl ethers in water at ng/L level by a simple DLLME-GC-(EI) MS method - Luís M. Madeira (2015)
Dispersive liquid-liquid microextraction (DLLME) is an extraction procedure gaining popularity in the recent years due to the easiness of operation, high enrichment factors, low cost and low consumption of organic solvents. This extraction method, prior to gas chromatography with mass spectrometry detection (GC-MS), was optimized for the determination of polybrominated diphenyl ethers (PBDEs) in aqueous samples. These were extracted with chlorobenzene (extraction solvent) and acetonitrile (dispersive solvent), allowing an enrichment factor of about 470 for BDE-100. The calibration curve for BDE-100 was linear in the range of 0.005-10 mu g/L, with an average reproducibility of 12% (RSD, %). The LOD, calculated by the signal-tonoise ratio, was 0.5 ng/L for BDE-100 and the recovery ranged from 91-107% for all spiked samples. Relative expanded uncertainty was concentration-dependent, reaching high values near the limit of quantification and decreasing until 14% for concentrations higher than 1 mu g/L of BDE-100. The dispersive liquid-liquid microextraction combined with gas chromatography with mass spectrometry detection (DLLME-GC-MS) method could be successfully applied to the determination of other PBDEs in water samples.